Gastroesophageal Foreign Bodies in Dogs - Endoscopy and Surgical Removal - Pinheiro Souto, Marcella; dos Santos Ribas, Priscila; Monteiro, Francisco Décio Oliveira; Corrêa da Silva, Amanda; Monteiro Barroso, João Pedro; Jales Gurgel, Heytor; Bueno Borges, Luisa Pucci; Maia Teixeira, Pedro Paulo (Acta Scientiae Veterinariae, 2023)
Background: Gastroesophageal foreign bodies (GFD) are commonly diagnosed in dogs and are considered an endoscopic emergency that, although not resulting in serious clinical sequelae or mortality, can compromise the health and well-being of the patient. The use of the digestive endoscopy for the diagnosis and treatment of GFD can be a valuable and viable alternative. There are cases of GFD in dogs for which the indicated treatment is surgery, which can be performed using minimally invasive or conventional techniques, associated or not with flexible endoscopy. The objective of this work is to describe 16 cases of GFD removal in dogs demonstrating the efficiency of upper digestive endoscopy. Cases: Of the 16 GFD cases, 63% (10/16) were male and 37% (6/16) female. Most aged under 1 year (63%), puppies (5/16) and juveniles (5/16). The patient with the lowest body weight was a miniature pinscher weighing 0.8 kg (Case 14) and the heaviest was an American Pit Bull Terrier weighing 28 kg (Case 11), the mean body weight of patients diagnosed with GFD was 10.2 ± 6.7 kg. Small and medium breeds were more affected, 44.7% (7/16) and 44.7% (7/16), respectively, and large breeds (Golden Retrievier and Bull Terrier), from cases 1 and 4, the least affected, 12.6% (2/16) of the cases. The 16 patients underwent a 12 h food fast and a 4 h water fast, as gastrointestinal emptying in these cases of GFD can be influenced by these foreign bodies. All underwent general inhalation anesthesia with monitoring of physiological parameters (temperature, heart rate, respiratory rate, oxygen saturation and blood pressure) before, during and after EGD, being positioned in left lateral decubitus. The 16 canine patients with suspected GFD underwent EGD for diagnostic confirmation and removal of foreign bodies. Five esophageal FB were diagnosed, 31% (5/16), and 11 gastric FB, 69% (11/16). The most frequently diagnosed foreign bodies were bone and tissue, 37.5% (6/16) and 31% (5/16). Other foreign bodies were materials such as plastics, metals, rubber, foam and stone. Of the 16 cases of GFD, EGD efficiently treated 88% (14/16) without the need for hospitalization, with only supportive treatment for the remission of complications caused by the presence of foreign bodies in the gastroesophageal tract. The main complications related to the presence of GFD were esophagitis in 25% (4/16) of cases, gastritis in 38% (6/16) and both alterations in 13% (2/16). Discussion: In this work, we can observe that more than a third of the clinical cases of treated dogs were diagnosed with GFD, demonstrating that these cases are common in the veterinary clinic. Most of these animals were males less than 1 year old. The improvement of learning in this category can lead these animals to exacerbated oral exploration of new objects. Most FBs were found in the stomach because they were of adequate size, consistency and shape for their passage through the esophagus, whereas esophageal FBs were all bone fragments of rigid consistency with diameters and sizes larger than the esophageal lumen. The interval between the ingestion of the object and the veterinary care can be decisive for the removal of the FB in the esophagus or stomach. Most gastric FBs removed were fabrics and plastics, flexible objects that can pass through the esophageal lumen more easily. Removal of GFD by endoscopy was performed with a high success rate, with only 2 cases being resolved by esophagostomy and gastrotomy. Flexible endoscopy proved to be an efficient technique for removing treated GFD, which can help remove FB during esophagotomy and be associated with rigid endoscopy. Patients recovered quickly and without complications, but it is important to emphasize that inadequate maneuvers and conducts can determine other outcomes. The use of endoscopy for GFD removal needs to be more popularized, as it can ensure better results for dogs treated with GFD. Keywords: digestive tract, endoscopic extraction, flexible endoscopy, ingested object, rigid endoscopy.